Peran Literasi Digital dan Motivasi Dalam Meningkatkan Produktivitas Kerja Karyawan Pada PT Cahaya Abadhi Sedjahtera Jakarta - Sara Sahrazad; Maria Cleopatra; Luluk Setyowati; Arief Muda Kusuma; Lengsi Manurung; Lusiana Wulansari; Adhis Darussalam Pamungkas; Deni Nasir Ahmad; Ade Nila Kamilia (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to determine the role of digital literacy and motivation in increasing employee productivity at PT. Cahaya Abadhi Sedjahtera Kramat Jati, East Jakarta. The research method used is qualitative. By means of observation, documentation, and interviews. The population in this study are employees who work at PT. Cahaya Abadhi Sedjahtera. Based on the results of the study, it can be concluded that based on the results of the study, it can be obtained that work motivation is a stage of increasing work productivity where employees are actually more productive at work. With work motivation and digital literacy, employees get more enthusiasm and encouragement to work so that employees can do their work more productively. By working more productively, it will increase income both for the company and for the employees themselves. The income in question is the result of cooperation between the company and the employees who are increasingly improving their skills at work..